Physical Performance Comparison between Under 15 Elite and Sub-Elite Soccer Players - Trecroci, Athos (J Hum Kinet, 2018)
The aim of this study was to compare the physical performance profile among young soccer players of different competitive levels. Two teams of elite (n = 22) and sub-elite (n = 22) soccer players at national (highly skilled) and regional (moderately skilled) level were recruited in the study. All participants were tested using a modified Illinois change of direction speed test, a T-drill with and without a ball, a countermovement jump, and a 10-m sprint. The analysis revealed significant differences in favor of elite players in sprint (d = 1.54, large) and vertical jump (d = 2.03, very large) outcomes, while no differences were observed in both modified Illinois change of direction speed (d = 0.16, trivial) and T-drill (d = 0.20, small) tests between the groups. The ability to change direction and speed with and without a ball was found not to be suitable enough to highlight the difference among youth players with moderate-to-high level of play. In conclusion, multi-testing approach based on task-related power should include vertical jump and sprint performance to delineate players of a higher level.